Serviços ecossistêmicos em áreas de borda do rio Cocó. Indicadores para o planejamento urbano de Fortaleza-Ce - Leite, Maria Emilia da Rocha Ferreira (2018)
The rapid and continuous growth of cities has brought a progressive environmental degradation of urban, in particular, the loss of ecosystem services benefits given to the inhabitants. Though, the traditional urban space planning has not taken into account the new challenges imposed on them and its inhabitants, specialy the ones resulting from the ecosystem services losses. Regarding to this cenario, this work aims to understand primarily the extention and the effects of this phennomenon and, afterwards, identify and assess the diferente processes related to ecosystem services. The purpose of this work is to study the relationship between Fortaleza and Cocó River whose interaction strongly influences the dynamics of urban expansion, shaping differents uses and occupation patterns to the boards. The research holds the Community of Dendê, placed in the right river bank, close to the mouth. We opted for a social and morphological analysis from the perspective of ecosystem services, which allows understanding the social-economics dimensions and physical-spatial aspects. The method consists in documental and iconographic survey, social and morphological indicators assessment, visits to the community and a participatory workshop to comprehend the importance given to ecosystem services. The results of research indicate that the Dendê Community residents of Dendê are conscious of growing urban space quality loss, but they do not associate this phenomen to the lack of ecosystem services. This fact drive us to conclude about the necessity of population conscientization by public policy to safeguard ecosystem benefits in urban áreas.